2011
DOI: 10.1177/1077558710394200
|View full text |Cite
|
Sign up to set email alerts
|

Review: Relation Between Quality-of-Care Indicators for Diabetes and Patient Outcomes: A Systematic Literature Review

Abstract: The authors conducted a systematic literature review to assess whether quality indicators for diabetes care are related to patient outcomes. Twenty-four studies were included that formally tested this relationship. Quality indicators focusing on structure or processes of care were included. Descriptive analyses were conducted on the associations found, differentiating for study quality and level of analysis. Structure indicators were mostly tested in studies with weak designs, showing no associations with surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 52 publications
1
56
0
3
Order By: Relevance
“…21 Although one would expect a relationship between annual monitoring and glycemic control, one should be aware that this will only occur when treatment of patients with elevated HbA1c level is subsequently improved or when patients with adequate levels deteriorate without annual monitoring. We observed a stronger predictive value for annual HbA1c monitoring on glycemic control in patients with elevated baseline levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Although one would expect a relationship between annual monitoring and glycemic control, one should be aware that this will only occur when treatment of patients with elevated HbA1c level is subsequently improved or when patients with adequate levels deteriorate without annual monitoring. We observed a stronger predictive value for annual HbA1c monitoring on glycemic control in patients with elevated baseline levels.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HbA1c monitoring and glycemic control has been tested, [17][18][19][20] but the results are inconclusive. 21 As these measures include all diabetes patients in the denominator, variations in the study population may influence the outcomes. There is no consensus on the recommended frequency of testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are different studies suggesting that either process or outcome indicators are most important for assessing clinical outcomes. [32][33][34][35][36][37][38][39] The results of this study provide more confidence in outcome than in process indicators from EMR. Regarding the validity of the indicators, we noticed that some outcome indicators could be improved.…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…Until now, whether a good QM system results in better process and outcome measures remains unclear. A meta-analysis of quality improvement strategies showed that interventions upon the entire system of chronic disease management were associated with improvements in (surrogate) patient outcomes (5), whereas a systematic review found that the structure of diabetes care was not associated with (surrogate) patient outcomes (25). The present study is the first to provide some insight into QM on an organizational level, but future study to explore the association between QM and patient outcomes is warranted.…”
Section: Resultsmentioning
confidence: 82%